2020
DOI: 10.1136/jitc-2020-001159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytokine release syndrome on cardiac function following CD19 CAR-T cell therapy in children and young adults with hematological malignancies

Abstract: BackgroundChimeric antigen receptor (CAR) T-cell-associated cytokine release syndrome (CRS) may present with tachycardia, hemodynamic instability and reduced cardiac function. Pediatric CAR studies examining cardiac toxicity are limited.MethodsWe report on cardiac toxicity observed in children and young adults with hematologic malignancies enrolled in a CD19-28ζ CAR T-cell phase I trial (NCT01593696). All patients had a formal baseline echocardiogram. Real-time studies included echocardiograms on intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 29 publications
1
79
0
Order By: Relevance
“…In the ELIANA trial, 29% of patients developed hypotension, and 17% were grade 3–4 ( Table 1 and Table 4 ) [ 8 ]. Other studies of pediatric and young adult patients have found that 18–38% of patients will develop grade 3–4 hypotension ( Table 5 ) [ 8 , 24 , 25 , 26 , 27 ], with 13–27% of these patients requiring vasopressor support [ 24 , 25 , 28 , 29 ], and up to one-third of patients requiring admission to the intensive care unit (ICU) [ 25 ]. In a retrospective study by Fitzgerald et al, 13 patients that developed cardiovascular toxicity developed fluid-refractory shock that necessitated the use of alpha agonists.…”
Section: Cardiotoxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…In the ELIANA trial, 29% of patients developed hypotension, and 17% were grade 3–4 ( Table 1 and Table 4 ) [ 8 ]. Other studies of pediatric and young adult patients have found that 18–38% of patients will develop grade 3–4 hypotension ( Table 5 ) [ 8 , 24 , 25 , 26 , 27 ], with 13–27% of these patients requiring vasopressor support [ 24 , 25 , 28 , 29 ], and up to one-third of patients requiring admission to the intensive care unit (ICU) [ 25 ]. In a retrospective study by Fitzgerald et al, 13 patients that developed cardiovascular toxicity developed fluid-refractory shock that necessitated the use of alpha agonists.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Patients with cardiac dysfunction in this study were more likely to have earlier CRS, more severe CRS, receive tocilizumab, and have a lower baseline global longitudinal strain (GLS). In this patient cohort, of the 37 patients that developed CRS, 9 (24%) developed hypotension requiring vasopressors, with 3 of these patients requiring two or more vasopressor agents [ 28 ].…”
Section: Cardiotoxicitymentioning
confidence: 99%
See 3 more Smart Citations